2008
DOI: 10.1038/eye.2008.55
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab for treatment of chronic central serous chorioretinopathy

Abstract: Sir, Response to Dr Sanjay et al We wish to thank Sanjay et al for spotting the typo in our report on the awareness and use of nutritional supplementations for patients with age-related macular degeneration. We stand corrected: only 9.2-30% were familiar with this condition as a cause for loss of vision. We would like to take this opportunity to congratulate our colleagues in Singapore for their excellent work in furthering the dissemination of information on this critically important topic and hope that their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 8 publications
0
24
0
2
Order By: Relevance
“…But aqueous VEGF is not significantly elevated in eyes with CSC. 16,[23][24][25] Moreover, there appears to be significant individual variation in treatment responses to IVB. 9,20 CSC encompasses a wide range of patients with varying degrees and patterns of angiographical and tomographical manifestations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But aqueous VEGF is not significantly elevated in eyes with CSC. 16,[23][24][25] Moreover, there appears to be significant individual variation in treatment responses to IVB. 9,20 CSC encompasses a wide range of patients with varying degrees and patterns of angiographical and tomographical manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Intravitreal bevacizumab (IVB), a recombinant humanized monoclonal anti-VEGF antibody, has been reported to be effective in CSC patients with symptom durations over 3 months. 9,[15][16][17][18][19][20] In acute CSC of o3 months symptom duration, IVB may not result in therapeutic benefits compared with simply waiting for spontaneous resolution. 21,22 It is not clear why and how IVB induces the absorption of subretinal fluid (SRF) in CSC.…”
Section: Introductionmentioning
confidence: 99%
“…Artunay and colleagues in a prospective open labeled non randomized trial comprising of 30 eyes with chronic symptomatic CSC reported significant improvement with single injection Bevacizumab. 15 In a retrospective analysis Kim et al noted that good responders to Avastin had smaller lesions and thicker choroids. 16 However Liu et al in a meta-analysis and review concluded that there was insufficient evidence for the superiority of Bevacizumab over other modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Intravitreal anti-vascular endothelium growth factor (anti-VEGF) therapy with bevacizumab has been reported with favorable results in case series, particularly in patients with chronic disease (53)(54)(55)(56)(57)(58)(59). Reduction of choroidal hyperpermeability has been proposed as a mechanism, as VEGF plays a role in the maintenance of choroidal vascular permeability, and recent data demonstrate that the choroid is abnormally thickened in these patients (60,61).…”
Section: Treatmentmentioning
confidence: 99%